Pro- and anti-inflammatory cytokines: the hidden keys to autoimmune gastritis therapy - Cascetta, Greta; Colombo, Giorgia; Eremita, Gianmarco; Garcia, Joe G. N.; Lenti, Marco Vincenzo; Di Sabatino, Antonio; Travelli, Cristina (Frontiers in Pharmacology, 2024)
Autoimmune gastritis (AIG) is an autoimmune disorder characterized by the destruction of gastric parietal cells and atrophy of the oxyntic mucosa which induces intrinsic factor deficiency and hypoachlorhydria. AIG predominantly affects the antral mucosa with AIG patients experiencing increased inflammation and a predisposition toward the development of gastric adenocarcinoma and type I neuroendocrine tumors. The exact pathogenesis of this autoimmune disorder is incompletely understood although dysregulated immunological mechanisms appear to major contributors. This review of autoimmune gastritis, an unmet medical need, summarizes current knowledge on pro-and anti-inflammatory cytokines and strategies for the discovery of novel biomarkers and potential pharmacological targets.